Cultural placemaking in the black suburbs of the tourist city - Raposo, O.; Nofre, J. (Journal of Urbanism, 2024)
This article examines how non-institutional(ized) street art tours and DIY parties in two racialized, lower-class neighborhoods in the outskirts of Lisbon generate different results. In the neighborhood of Quinta do Mocho, these street art tours and DIY parties arise as playfulness and multicultural experiences of opening up the communities to local white middle-class visitors and tourists. In the neighborhood of Cova da Moura, these actions culminate in a cultural festival that celebrates African and Afro-diasporic cultures, promoting the visibility of the talented artists of the neighborhood. In both cases, positive representations about these territories are produced, linked to a strengthening of the sense of belonging to Quinta do Mocho’s and Cova de Moura’s communities. The article concludes by suggesting that non-institutional(ized) street art tours and DIY parties arise as pioneering actions toward challenging and decolonizing urban thinking on contemporary Lisbon.